Reestructuración técnica en la línea agrícola y administrativa de la empresa A & P de Colombia S.A.S. (2018)
It begins with an external diagnosis in which it is determined through PESTAL analysis, that the company is not prepared to face the current market, due to its limited capacity to potentiate the current opportunities to increase competitiveness, in addition to the tool of the Chamber of Commerce, an information flow was determined in the administrative processes, in addition to the disarticulation of the objectives and organizational goals. In the technical study, a number of recordings were identified that do not generate value to the product, the installed capacities of the machine do not correspond with the capacity necessary to meet the demand, which is generating problems of excessive inventory, material in process and finished product , which show inadequate methods of work and distribution in the plant with the account of the company A & P DE COLOMBIA SAS, for which the technical restructuring of the agricultural line was carried out through the application of tools for continuous improvement such as the 5 production planning, among others.